Biallelic Variants in UBA5 Link Dysfunctional UFM1 Ubiquitin-like Modifier Pathway to Severe Infantile-Onset Encephalopathy - Muona, Mikko (Am J Hum Genet, 2016)
The ubiquitin fold modifier 1 (UFM1) cascade is a recently identified evolutionarily conserved ubiquitin-like modification system whose function and link to human disease have remained largely uncharacterized. By using exome sequencing in Finnish individuals with severe epileptic syndromes, we identified pathogenic compound heterozygous variants in UBA5, encoding an activating enzyme for UFM1, in two unrelated families. Two additional individuals with biallelic UBA5 variants were identified from the UK-based Deciphering Developmental Disorders study and one from the Northern Finland Intellectual Disability cohort. The affected individuals (n = 9) presented in early infancy with severe irritability, followed by dystonia and stagnation of development. Furthermore, the majority of individuals display postnatal microcephaly and epilepsy and develop spasticity. The affected individuals were compound heterozygous for a missense substitution, c.1111G>A (p.Ala371Thr; allele frequency of 0.28% in Europeans), and a nonsense variant or c.164G>A that encodes an amino acid substitution p.Arg55His, but also affects splicing by facilitating exon 2 skipping, thus also being in effect a loss-of-function allele. Using an in vitro thioester formation assay and cellular analyses, we show that the p.Ala371Thr variant is hypomorphic with attenuated ability to transfer the activated UFM1 to UFC1. Finally, we show that the CNS-specific knockout of Ufm1 in mice causes neonatal death accompanied by microcephaly and apoptosis in specific neurons, further suggesting that the UFM1 system is essential for CNS development and function. Taken together, our data imply that the combination of a hypomorphic p.Ala371Thr variant in trans with a loss-of-function allele in UBA5 underlies a severe infantile-onset encephalopathy.